2008
DOI: 10.1016/j.cell.2008.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic IKKβ/NF-κB and ER Stress Link Overnutrition to Energy Imbalance and Obesity

Abstract: SUMMARY Overnutrition is associated with chronic inflammation in metabolic tissues; however, whether metabolic inflammation compromises the neural regulatory systems and therefore promotes overnutrition-associated diseases remains unexplored. Our results demonstrate that a mediator of metabolic inflammation, IKKβ/NF-κB, normally remains inactive although enriched in the hypothalamic neurons; however, overnutrition atypically activates hypothalamic IKKβ/NF-κB at least through elevated endoplasmic reticulum stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

48
1,336
3
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,239 publications
(1,455 citation statements)
references
References 38 publications
48
1,336
3
14
Order By: Relevance
“…From these data, we conclude that changes in gut microbiota and changes in gut permeability could be signaled directly to the brain via the vagus nerve and that chronic exposure to low-level LPS could lead to the development of leptin resistance in VAN. It is unclear whether LPS could induce leptin resistance in the arcuate nucleus. There is evidence that proinflammatory signals in the hypothalamus result in impaired leptin signaling (35) and that NF-B signaling, an important downstream effector of LPS, induces SOCS-3 expression in the arcuate nucleus (37). Our data shed no light on the matter and suggest only that LPS levels are insufficient following 8 wk ingestion of a HF diet in Sprague-Dawley rats to effect leptin signaling in the arcuate nucleus.…”
Section: Discussioncontrasting
confidence: 47%
“…From these data, we conclude that changes in gut microbiota and changes in gut permeability could be signaled directly to the brain via the vagus nerve and that chronic exposure to low-level LPS could lead to the development of leptin resistance in VAN. It is unclear whether LPS could induce leptin resistance in the arcuate nucleus. There is evidence that proinflammatory signals in the hypothalamus result in impaired leptin signaling (35) and that NF-B signaling, an important downstream effector of LPS, induces SOCS-3 expression in the arcuate nucleus (37). Our data shed no light on the matter and suggest only that LPS levels are insufficient following 8 wk ingestion of a HF diet in Sprague-Dawley rats to effect leptin signaling in the arcuate nucleus.…”
Section: Discussioncontrasting
confidence: 47%
“…To elucidate the mechanism involved in the effect of ARA on central leptin resistance, we also It has been suggested that hypothalamic inflammation could be an important mediator of HFD-induced leptin resistance [11,38]. In the present study, the pro-inflammatory markers TNF-α, IL-1β, IL-6, and pIκBα were up-regulated at the hypothalamus by central ARA administration, suggesting that central ARA administration is sufficient to induce hypothalamic inflammation.…”
Section: Discussionsupporting
confidence: 53%
“…The JAK2-STAT3 pathway has been shown to mediate the effect of leptin on glucose metabolism [8], and the PI3K-Akt pathway is involved in both glucose [9] and lipid metabolism [10]. Recent studies have provided strong evidence for the contribution of hypothalamic inflammation to HFD-induced leptin resistance and/or type 2 diabetes mellitus [11,12].…”
mentioning
confidence: 99%
“…We have previously shown that SOCS3 expression is Cre-dependent, and its expression is upregulated approximately twofold in Cre-expressing cells upon recombination (6). The Tg.Agrp-Cre mice have been used and validated in a number of independent studies (7,(25)(26)(27)(28)(29)(30)(31). The resultant mutant mice, termed AgRP-SOCS3-OE, were born in Mendelian ratio with no detectable gross abnormalities.…”
Section: Expression Of Socs3 In Agrp Neurons Is Dynamically Modulated Inmentioning
confidence: 99%
“…Conversely, up-regulation of SOCS3 in POMC neurons of chow-fed mice leads to increased body adiposity (6). In addition, wide-spread up-regulation of SOCS3 has been shown to be associated with neuronal inflammation in diet-induced obese animals (7). Thus SOCS3, which is up-regulated in chronic obesity, is commonly thought to play a pathophysiological role in obesity-associated leptin resistance.…”
mentioning
confidence: 99%